Tufted angioma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
A 17-month-old boy was first observed due to a lesion of the right buttock. His parents reported that they saw first time at the age of 5 months on the buttoch a violaceous, warmer than normal tumefaction, which later on persisted. On physical examination, the right buttock was 20% larger than the left one. On its surface there were reddish points and striae. Its skin was warmer and its consistency was slightly increased. There was also a scar of a previous biopsy (Fig. 1). The observation of a histological slide given by his parents showed in the deep dermis and in the upper subcutaneous fat islets of angiopoietic tissue in a "cannonball" pattern (Fig. 2), consisting of capillaries with plump endothelial cells and pericytes. There were not atypical cells (Fig. 3). These findings led to the final diagnosis of tufted angioma. A period of clinical observation was proposed.